P160 A novel PillCam Crohn's capsule score (Eliakim score) for quantification of mucosal inflammation in Crohn's disease. (15th January 2020) - Eliakim, R; Yablecovitch, D; Lahat, A; Ungar, B; Shachar, E; Carter, D; Selinger, L; Neuman, S; Ben-Horin, S; Kopylov, U
Abstract: Background: Capsule endoscopy (CE) is an important modality for monitoring of Crohn's disease (CD). We recently established that small bowel (SB) inflammation on CE quantified by a Lewis score >350 accurately predicts risk of relapse within 2 years in CD patients in clinical remission. Recently, a novel pan-enteric capsule (PillCam Crohn's (PCCE), Medtronic, USA) was approved for use. However, no quantitative index for pan-enteric PCCE is currently available. The current study was undertaken as a sub-study of a prospective randomised controlled CURE-CD trial aiming to optimise treatment of CD patients in remission using a PCCE- based treat-to-target approach; the aim of this ancillary study was to compare the correlation and reliability of the novel PCCE inflamatory score (Eliakim score) with the Lewis score as performed by 2 independent experienced CE readers. Methods: The study cohort includes CD patients in clinical remission (CDAI<150). The patients were prospectively enrolled and underwent patency capsule evaluation; if excreted within 30 h, PCCE was performed following bowel preparation. PCCE was repeated every 6 months; if no colonic disease was detected on first PCCE, subsequent examinations were performed without colonic preparation. Each PCCE was independently reviewed by 2 experienced readers (RE (reader 1);UK (reader 2)). All studies were scored using the Lewis score and Eliakim score (comprised of a sum of scores for most common and most severe lesions multiplied by percentage of involvement per bowel segment (3 for small bowel and 2 for colon) with an additional stricture score). Pearson's and Spearman' correlation, Cohen's kappa and inter-rater reliability coefficient (IRC) between the scores and the readers were calculated as appropriate. Results: Forty PCCE exams were included. The median LS was 225 for both readers (interquartile range (IQR)—157–815 for reader 1, 33- 1125 for reader 2). Both readers identified significant SB inflammation (LS>350) in 17/40 (42.5%) of the patients with strong agreement between the readers (Spearman's r = 0.87, p < 0.0001). The median PCCE score was 6 (4–14.75) and 4 (2–14.75) for reader 1 and 2, respectively. There was a high IRC between the two readers for LS (0.88, p < 0.0001 for absolute agreement) and PCCE score (0.91, p < 0.0001). For the small bowel, the correlation between LS and PCCE was moderate for reader 1 (Pearson's r = 0.72, p < 0.0001 and strong for reader 2 Pearson's r = 0.84, p < 0.0001). Conclusion: There is a need for a quantitative pan-enteric score for the novel Pillcam Crohns capsule. The presently proposed score, while mandating further clinical validation, has strong inter-reader reliability and moderate-to-strong correlation with the validated small bowel capsule score (LS)